Efficient phosphorescent water-soluble composite material and preparation method of efficient phosphorescent water-soluble composite material with semiconductor nanocrystal sensitization characteristic

By using composite materials of water-soluble zinc oxide nanocrystals and carbon nanodots, the application of existing phosphorescent materials in the field of bioimaging is solved, and the bioimaging effect of efficient phosphorescence is achieved.

CN119505892APending Publication Date: 2025-02-25ZHOUKOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665332.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The application of existing room temperature phosphorescent materials in the field of bioimaging is limited by the problems of high production costs, poor biocompatibility, large cytotoxicity and complex preparation processes, and the phosphorescence efficiency of phosphorescence carbon nanodots is low.

Method used

The composite material of water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots was prepared by phosphoric acid and microwave heating, and zinc oxide nanocrystals were prepared by mixing reactions of Zn(Ac)2∙2H2O and KOH solution. The two were mixed to form a highly efficient phosphorescence water-soluble composite material.

Benefits of technology

It significantly enhances the phosphorescence intensity and life of composite materials, facilitates its application in the field of biological imaging, and improves the effects of biological experimental research, clinical diagnosis and pathological research.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505892A_ABST
    Figure CN119505892A_ABST
Patent Text Reader

Abstract

The invention relates to a high-efficiency phosphorescent water-soluble composite material and a preparation method of the high-efficiency phosphorescent water-soluble composite material with semiconductor nanocrystal sensitization characteristic, the composite material comprises water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots, and the preparation method comprises the following steps: firstly, preparing phosphorescent carbon nanodots through phosphoric acid and a microwave heating method; then carrying out water-soluble treatment on the phosphorescent carbon nanodots; the preparation method comprises the following steps: preparing zinc oxide nanocrystals through a mixed reaction of Zn (Ac) 22H2O and a KOH solution, carrying out water-soluble treatment on the zinc oxide nanocrystals to respectively obtain water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots, and mixing the water-soluble zinc oxide nanocrystals and the water-soluble carbon nanodots to obtain the efficient phosphorescent water-soluble composite material. When the composite material is made into an aqueous solution and is practically compared with single phosphorescent carbon nanodots, the phosphorescent intensity of the composite material is obviously enhanced, the phosphorescent service life is greatly prolonged, and the characteristics of the phosphorescent intensity and service life of the composite material are beneficial to the application of the composite material in the field of biological imaging. The method has important significance in important livelihood fields such as biological experiment research, clinical diagnosis and pathological research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon nano material preparation and luminescent material preparation, and particularly relates to a high-efficiency phosphorescent water-soluble composite material and a preparation method of the high-efficiency phosphorescent water-soluble composite material with semiconductor nanocrystal sensitization characteristics. Background Art

[0002] Room temperature phosphorescent (RTP) materials are one of the most popular types of delayed luminescence and have important application value in optoelectronic devices, photocatalysis, anti-counterfeiting, sensing, security systems, and especially in the field of bioimaging. Phosphorescent bioimaging of RTP materials with long luminescence lifetime and large Stokes shift does not require real-time excitation from an external light source, and can effectively reduce the background interference of spontaneous fluorescence of biological tissues to achieve high-resolution optical bioimaging. Therefore, RTP materials are an ideal optical imaging agent and a long-standing pursuit in the field of bioimaging. At present, most RTP materials are organometallic complexes and crystalline organic compounds. However, most of these materials are in the solid state and have problems such as high production cost, poor biocompatibility, high cytotoxicity and complex preparation process, which seriously limit their application in phosphorescent bioimaging.

[0003] Carbon nanodots have good stability, crystallinity, easy adjustment of luminescence wavelength, high chemical stability, good biocompatibility, excellent optical properties, easy availability of raw materials and simple preparation, and have attracted much attention. In recent years, after continuous research by technicians, some room temperature phosphorescent carbon nanodots have been prepared. This provides a new path for the development of new non-toxic and efficient phosphorescent imaging agents. With the development of technology, the phosphorescence efficiency of phosphorescent carbon nanodots has been improved, but its phosphorescence efficiency is still relatively low, which limits its application in the field of room temperature phosphorescent imaging. Summary of the invention

[0004] The purpose of the present invention is to solve the above problems and to provide a high-efficiency phosphorescent water-soluble composite material and a method for preparing the high-efficiency phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics.

[0005] The technical solution of the present invention is: a high-efficiency phosphorescent water-soluble composite material, characterized in that: the composite material comprises zinc oxide nanocrystals and carbon nanodots, and according to mass calculation, the mass of the zinc oxide nanocrystals: the mass of the carbon nanodots is 1-8:8; the zinc oxide nanocrystals are water-soluble zinc oxide nanocrystals, and the carbon nanodots are water-soluble carbon nanodots.

[0006] Preferably, the composite material is a liquid, and water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots are dissolved in deionized water to form a mixed solution, and the mass concentration of zinc oxide nanocrystals: mass concentration of carbon nanodots is 1-8:8.

[0007] Preferably, in the mixed solution, the mass concentration of the zinc oxide nanocrystal aqueous solution is 15-120 μg / mL; the mass concentration of the carbon nanodot aqueous solution is 120 μg / mL.

[0008] A method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics comprises the following steps: a. Preparation of water-soluble zinc oxide nanocrystals; b. Preparation of water-soluble carbon nanodots; c. Mix According to the ratio of zinc oxide nanocrystal mass to carbon nanodot mass of 1-8:8, the materials obtained in step a and step b are mixed to obtain a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics.

[0009] Preferably, the step a further comprises the following steps: Dissolving the zinc oxide nanocrystals obtained in step a into deionized water to prepare a zinc oxide nanocrystal aqueous solution; The step b also includes the following steps: b1. The phosphorescent carbon nanodots obtained in step a are dissolved in deionized water to prepare a phosphorescent carbon nanodot aqueous solution; the step c is replaced by the following steps: c1. According to the mass concentration of zinc oxide nanocrystals: carbon nanodots, the mass concentration is 1 to 8:8, the solutions obtained in steps a1 and b1 are mixed, and the water-soluble carbon nanodots in the solution are sensitized by zinc oxide nanocrystals and semiconductor nanocrystals to obtain an efficient phosphorescent water-soluble composite material.

[0010] Preferably, the preparation process of water-soluble zinc oxide nanocrystals comprises the following steps: ① Solution preparation Disperse Zn(Ac)2 ∙2H2O in anhydrous ethanol and KOH in anhydrous ethanol to prepare their respective alcohol solutions, dissolving and dispersing the precursors; ②Mixed reaction The KOH alcohol solution is added to the Zn(Ac)2 ∙2H2O alcohol solution, and the stirring is continued for T1 to form a mixed solution. The precursors are mixed and reacted to prepare alcohol-soluble zinc oxide; ③ Water-soluble modification APTES is added to the mixed solution and stirred continuously for T2 time. APTES, which is the full name of 3-aminopropyltriethoxysilane, is used to enhance the hydrophilicity of zinc oxide nanocrystals and achieve water-soluble modification.

[0011] ④ Precipitation and centrifugation to obtain crude zinc oxide nanocrystals; ⑤ Wash the crude zinc oxide nanocrystals with anhydrous ethanol at least three times to purify and remove impurities and unreacted precursors; ⑥ Drying to obtain water-soluble zinc oxide nanocrystalline powder.

[0012] Preferably, the preparation process of the Zn(Ac)2 ∙2H2O alcohol solution is that 5.5 g Zn(Ac)2 ∙2H2O is dispersed in 150 mL anhydrous ethanol, and the preparation process of the KOH alcohol solution is that 2.0 g KOH is dispersed in 20 mL anhydrous ethanol; the time T1 is 4 hours, the time T2 is 3 hours, and the drying temperature in step ⑥ is 70 °C.

[0013] Preferably, the water-soluble carbon nanodots preparation process comprises the following steps: A. Solution Preparation First dissolve ethylenediamine in deionized water. B. Carbonization to form carbon nanodots Then add phosphoric acid to the deionized water and stir for T3 to form a transparent solution A, and stir to fully mix the ethylenediamine and phosphoric acid; put the transparent solution A into a microwave oven and heat it for T4 to carbonize the mixture in the solution; C. Dilution and centrifugation purification Take out in the microwave environment, cool the solution to room temperature, add deionized water to dilute the solution, dilute to make the carbon nanodots fully dissolved in water, easy to extract the carbon nanodots, centrifuge for T5 to take out the precipitate in the solution, and keep the liquid; D. After the liquid is filtered through a 0.22 μm ultrafiltration membrane, sodium carbonate is added to neutralize the acid in the liquid, that is, to remove the excess phosphoric acid therein, and the supernatant is collected and dialyzed for time T6, and further purified by dialysis; E. freeze-drying the dialyzed solution to obtain carbon nanodot powder; F. Silicon shell The aqueous solution of the carbon nanodot powder and tetraethoxysilane are dispersed in a deionized water support solution, and ammonia water is added to the solution to promote the hydrolysis of tetraethoxysilane and accelerate the process of wrapping the silicon shell. Stir at room temperature for time T7, and collect the transparent solution B; G. The transparent solution B is filtered and purified at least twice through a 0.22 μm ultrafiltration membrane to obtain a water-soluble carbon nanodot solution, and the solution is dried to obtain a water-soluble carbon nanodot powder.

[0014] Preferably, in the step A, 1 mL of ethylenediamine is dissolved in 15 mL of deionized water, 2 mL of phosphoric acid is added in the step B, and the stirring time T3 is 30 minutes; the heating time T4 in the microwave is 120 seconds; in the step C, 20 mL of deionized water is added for dilution, and the centrifugation time T5 is 10 minutes; the dialysis time in the step D is one week, and the dialysis is performed using a membrane with a MWCO of 500 Da.

[0015] Preferably, in the step, 0.1 mg / mL phosphorescent carbon nanodot aqueous solution and 0.5 mL tetraethoxysilane are dispersed in 15 mL deionized water to form a solution, 0.5 mL of ammonia water is added to the solution, and the stirring time T7 is 8 hours.

[0016] The beneficial effects of the present invention are: The invention provides a high-efficiency phosphorescent water-soluble composite material and a preparation method of the high-efficiency phosphorescent water-soluble composite material with semiconductor nanocrystal sensitization characteristics. The composite material comprises water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots. The phosphorescent carbon nanodots are firstly prepared by phosphoric acid and microwave heating, and then the phosphorescent carbon nanodots are treated for water solubility. Meanwhile, zinc oxide nanocrystals are prepared by a mixed reaction of Zn(Ac)2∙2H2O and KOH solution, and then the zinc oxide nanocrystals are treated for water solubility, so that water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots are obtained respectively. The high-efficiency phosphorescent water-soluble composite material is obtained after the two are mixed. The composite material is made into an aqueous solution and compared with the single phosphorescent carbon nanodots for practical use. The phosphorescence intensity of the composite material is significantly enhanced, and the phosphorescence life is greatly prolonged. The characteristics of the phosphorescence intensity and life of the composite material are conducive to its application in the field of biological imaging, and have important significance for major livelihood fields such as biological experimental research, clinical diagnosis, and pathological research. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The phosphorescence spectra of carbon nanodots in a mixed solution of 2 mL of carbon nanodot solution and 2 mL of zinc oxide nanocrystal solution of different concentrations in Example 5; Figure 2 is a phosphorescence lifetime graph at 520 nm of a mixed solution of 2 mL of carbon nanodot solution and 2 mL of zinc oxide nanocrystal solution of different concentrations in Example 5; Figure 3 This is a comparison photo of phosphorescence attenuation of a mixed solution of 2 mL of carbon nanodot solution and 2 mL of zinc oxide nanocrystal solution of different concentrations in Example 5; Figure 4 It is the fluorescence spectrum of the mixed solution of 2 mL zinc oxide nanocrystal solution and 2 mL carbon nanodot solution of different concentrations under ultraviolet light irradiation in the principle analysis experiment; Figure 5It is the fluorescence lifetime diagram of the mixed solution of 2 mL zinc oxide nanocrystal solution and 2 mL carbon nanodot solution of different concentrations under ultraviolet light irradiation in the principle analysis experiment; Figure 6 It is a schematic diagram of the Zeta potential of zinc oxide nanocrystals and carbon nanodots; Figure 7 Schematic diagram of triplet exciton transfer mechanism between zinc oxide nanocrystals and carbon nanodots in mixed solution; Figure 8 This is the transmission electron microscopy spectrum of a single carbon nanodot solution; Fig. 9 This is a transmission electron microscope image of a single zinc oxide nanocrystal solution; Fig.10 This is a transmission electron microscope image of a mixed solution of carbon nanodots and zinc oxide nanocrystals; Fig.11 Schematic diagram of the preparation of highly efficient phosphorescent water-soluble composite materials; Fig.12 It is a comparison of biological imaging of a single solution phosphor of carbon nanodots and a mixed solution phosphor of the present patent with the same concentration of carbon nanodots; Fig.13 This is a printing comparison chart of the phosphorescent ink of a single solution of carbon nanodots with the same concentration of carbon nanodots and the phosphorescent ink of the mixed solution in this patent. DETAILED DESCRIPTION

[0018] Embodiment 1: A highly efficient phosphorescent water-soluble composite material, comprising zinc oxide nanocrystals and carbon nanodots. Calculated by mass, the mass of the zinc oxide nanocrystals: the mass of the carbon nanodots is 1-8:8; the zinc oxide nanocrystals are water-soluble zinc oxide nanocrystals, and the carbon nanodots are water-soluble carbon nanodots.

[0019] The composite material in the first embodiment can be prepared by the method in the fourth embodiment, or by other methods in the prior art, as long as the zinc oxide nanocrystals and carbon nanodots are the same as those prepared in the embodiment.

[0020] Embodiment 2: The composite material is a liquid, and water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots are dissolved in deionized water at the same time, and the mass concentration of zinc oxide nanocrystals: mass concentration of carbon nanodots is 1-8:8.

[0021] The second embodiment is to make the composite material in the first embodiment into a liquid to form a liquid reagent, which is convenient for direct use.

[0022] Example 3: Example 3 is basically the same as Example 2, and the similarities are not repeated. The difference is that the mass concentration of the zinc oxide nanocrystals in the aqueous solution described in Example 3 is 15-120 μg / mL; the mass concentration of the carbon nanodots in the aqueous solution is 120 μg / mL.

[0023] Embodiment 4: A method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics, comprising the following steps: a. Preparation of water-soluble zinc oxide nanocrystals; b. Preparation of water-soluble carbon nanodots; c. Mix According to the ratio of zinc oxide nanocrystal mass to carbon nanodot mass of 1-8:8, the materials obtained in step a and step b are mixed to obtain a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics.

[0024] The water-soluble zinc oxide nanocrystal preparation process comprises the following steps: ① Solution preparation Disperse 5.5 g Zn(Ac)2 ∙2H2O in 150 mL anhydrous ethanol and 2.0 g KOH in 20 mL anhydrous ethanol to prepare their respective alcohol solutions; ②Mixed reaction The KOH alcohol solution was added to the Zn(Ac)2 ∙2H2O alcohol solution, and the stirring time T1 was 4 hours to form a mixed solution; ③ Water-soluble modification APTES was added to the mixed solution and the continuous stirring time T2 was 3 hours. ④ Precipitation and centrifugation to obtain crude zinc oxide nanocrystals; ⑤ Wash the crude zinc oxide nanocrystals at least three times with anhydrous ethanol to remove impurities; ⑥ Drying in 70 ℃ environment to obtain water-soluble zinc oxide nanocrystalline powder.

[0025] The water-soluble carbon nanodot preparation process comprises the following steps: A. Solution Preparation First, dissolve 1 mL of ethylenediamine in 15 mL of deionized water. B. Carbonization to form carbon nanodots Then add 2 mL of phosphoric acid into the deionized water and stir for 30 minutes to form a transparent solution A; put the transparent solution A into a microwave environment and heat it for 120 seconds to carbonize the mixture in the solution; C. Dilution and centrifugation purification Take it out in the microwave environment, cool the solution to room temperature, add 20 mL of deionized water to dilute the solution, centrifuge for 10 minutes T5 to remove the precipitate in the solution, and keep the liquid; D. After the liquid was filtered through a 0.22 μm ultrafiltration membrane, sodium carbonate was added to neutralize the acid in the liquid, and the supernatant was collected and dialyzed using a membrane with a MWCO of 500 Da for a period of one week.

[0026] E. freeze-drying the dialyzed solution to obtain carbon nanodot powder; F. Silicon shell A 0.1 mg / mL phosphorescent carbon nanodot aqueous solution and 0.5 mL tetraethoxysilane were dispersed in 15 mL deionized water to form a solution, 0.5 mL of ammonia water was added to the solution, and the stirring time T7 was 8 hours at room temperature, and the transparent solution B was collected; G. After the transparent solution B is filtered at least twice through a 0.22 μm ultrafiltration membrane, a water-soluble carbon nanodot solution is obtained. After the solution is dried, a water-soluble carbon nanodot powder is obtained.

[0027] In the fourth embodiment, a method for preparing the composite material in the first embodiment is provided. The composite material obtained by the preparation method is a mixture of two materials. When used, the composite material is weighed according to the concentration requirement of the solution to be prepared, and then added to deionized water for dispersion and dissolution to obtain the liquid composite material in the second embodiment below. The powdered solid composite materials in the fourth embodiment and the first embodiment are more convenient for storage and transportation.

[0028] Embodiment 5: Embodiment 5 is basically the same as Embodiment 4, and the similarities are not repeated. The difference is that Embodiment 5 also includes the following steps: a1. The zinc oxide nanocrystals obtained in step a are dissolved in deionized water to prepare an aqueous solution of zinc oxide nanocrystals; The step b also includes the following steps: b1. The phosphorescent carbon nanodots obtained in step a are dissolved in deionized water to prepare a phosphorescent carbon nanodot aqueous solution; the step c is replaced by the following steps: c1. According to the mass concentration of zinc oxide nanocrystals: carbon nanodots, the mass concentration is 1 to 8:8, the solutions obtained in steps a1 and b1 are mixed, and the water-soluble carbon nanodots in the solution are sensitized by zinc oxide nanocrystals and semiconductor nanocrystals to obtain an efficient phosphorescent water-soluble composite material.

[0029] Verification of technical effects In order to verify the technical effect of improving the phosphorescence efficiency of the high-efficiency phosphorescent water-soluble composite material prepared by the method of Example 5, the inventors prepared aqueous zinc oxide nanocrystal solutions with weight concentrations of 0, 30, 60, 90, 120, 150, 180, 200, and 240 μg / mL respectively according to step a1; and prepared a 240 μg / mL water-soluble carbon nanodot solution according to step b1, and then took 2 mL of zinc oxide nanocrystal solutions of different concentrations and 2 mL of carbon nanodot solutions and mixed them, and used zinc oxide nanocrystals and semiconductor nanocrystals to sensitize the water-soluble carbon nanodots in the solution to form a composite material, and performed relevant tests on each mixed solution.

[0030] like Figure 1 The phosphorescence spectrum of carbon nanodots in the mixed solution of 2 mL carbon nanodot solution and 2 mL zinc oxide nanocrystal solution of different concentrations shows that the phosphorescence intensity of the composite material gradually increases with the increase of the concentration of zinc oxide nanocrystals, and the phosphorescence intensity of the mixed solution is the maximum when the concentration of zinc oxide nanocrystals before mixing is as high as 200 μg / mL. When the weight of zinc oxide nanocrystals in the mixed solution is 30:240, the intensity of phosphorescence is about 45% higher than that without zinc oxide; when the weight of zinc oxide nanocrystals in the solution is 60:240, the intensity of phosphorescence is about 100% higher; when the weight of zinc oxide nanocrystals in the solution is 200:240, the intensity of phosphorescence is about 550% higher.

[0031] like Figure 2 The phosphorescence lifetime spectrum at 520 nm of a mixed solution of 2 mL of carbon nanodot solution and 2 mL of zinc oxide nanocrystal solution with different concentrations is shown in Figure 5; the phosphorescence lifetime of the mixed solution gradually increases with the increase in the concentration of added zinc oxide nanocrystals, and the phosphorescence lifetime of the mixed solution is the longest, reaching 1.45 s, when the concentration of zinc oxide nanocrystals is as high as 200 μg / mL.

[0032] like Figure 3 The comparative digital photos of the phosphorescence decay of a mixed solution of 2 mL of carbon nanodot solution and 2 mL of zinc oxide nanocrystal solution with different concentrations after excitation by 365nm ultraviolet light are shown as follows; the phosphorescence lifetime and intensity of the mixed solution both increase with the increase of the concentration of added zinc oxide nanocrystals.

[0033] from Figure 1-2 -3, it can be concluded that the phosphorescence efficiency of the mixed solution increases with the increase of the concentration of added zinc oxide nanocrystals, up to 39%.

[0034] Experimental analysis of the principle of effect In order to deeply analyze the principle behind the above-mentioned improvement in phosphorescence efficiency, the inventors prepared an aqueous solution of zinc oxide nanocrystals with a weight concentration of 240 μg / mL; at the same time, they prepared water-soluble carbon nanodot solutions with weight concentrations of 0, 30, 60, 90, 120, 150, 180, 200, and 240 μg / mL, and then took 2 mL of zinc oxide nanocrystal solution and 2 mL of carbon nanodot solutions of different concentrations and mixed them, and carried out relevant tests on each mixed solution.

[0035] Figure 4 is the fluorescence spectra of these mixed solutions under ultraviolet light; Figure 4 It can be observed that after introducing different concentrations of carbon nanodot solutions into the zinc oxide nanocrystal solution, as the concentration of carbon nanodots introduced into the mixed solution increases, the fluorescence intensity of the zinc oxide nanocrystals gradually decreases until it is quenched; Figure 5 The fluorescence lifetime diagram of the mixed solution of these solutions under ultraviolet light irradiation shows that the fluorescence lifetime of zinc oxide nanocrystals gradually shortens with the increase of the concentration of carbon nanodots in the mixed solution.

[0036] Figure 4 and Figure 5 Combined with the analysis, it is found that the fluorescence efficiency of zinc oxide nanocrystals in the mixed solution decreases with the increase of carbon nanodot concentration in the solution. Figure 1-2 -3 also found that the phosphorescence efficiency of the mixed solution increases with the increase in the concentration of zinc oxide nanocrystals. Combining the two rules, there is a phenomenon of one increasing while the other decreasing. And through UPS testing, it can be seen that the energy level position of the triplet exciton of zinc oxide nanocrystals (-4.83 eV) is slightly higher than the energy level position of the triplet exciton of carbon nanodots (-4.84 eV) (see Figure 7 Schematic diagram of triplet exciton transfer mechanism between zinc oxide nanocrystals and carbon nanodots in a mixed solution). The above results confirm that the triplet excitons of the zinc oxide nanocrystal energy donor in the mixed solution can be transferred to the triplet state of the carbon nanodot energy acceptor, with a transfer efficiency of up to 97.5%, which greatly increases the population of triplet excitons in carbon nanodots, thereby greatly improving the phosphorescence emission efficiency of carbon nanodots.

[0037] The inventor obtained a schematic diagram of the Zeta potential of zinc oxide nanocrystals and carbon nanodots - Figure 6 ; Transmission electron microscopy spectra of single carbon nanodot solution- Figure 8 ; Transmission electron microscopy of zinc oxide nanocrystal solution alone - Fig. 9 ; Transmission electron microscopy spectra of mixed solution of carbon nanodots and zinc oxide nanocrystals- Fig.10 ; Fig.11 Schematic diagram of the preparation of high-efficiency phosphorescent water-soluble composite materials. Figure 6The graph shows that the zinc oxide nanocrystals have a positive potential and the carbon nanodots have a negative potential, indicating that the two can be connected through electrostatic interaction. Fig.10 The figure also shows the connection between the two in the mixed solution, that is, the carbon nanodots are adsorbed around the zinc oxide nanocrystals to achieve mutual connection. The mutual connection between the two provides objective conditions for the aforementioned triplet exciton transfer. Fig.10 The red dotted circle in the middle is zinc oxide, and the white dotted circle is carbon nanodots; therefore, the technical effect of the present invention is supported by the physical principles behind the mixing of the two materials in a solution.

[0038] The water-soluble zinc oxide nanocrystals in this patent can also be called semiconductor nanocrystals, and the water-soluble carbon nanodots in this patent are phosphorescent materials. Therefore, the inventors call the process of transferring triplet excitons from zinc oxide nanocrystals to carbon nanodots in the mixed solution mentioned in this patent the sensitization of carbon nanodots by semiconductor nanocrystals to enhance the phosphorescence efficiency, and the methods of Examples 4 and 5 are called methods for preparing high-efficiency phosphorescent water-soluble composite materials with semiconductor nanocrystal sensitization characteristics.

[0039] The composite material in this patent has good water solubility and biocompatibility and can be applied to phosphorescence imaging of biological tissues, such as Fig.12 As shown, CNDs represents the phosphor of a single carbon nanodot solution, CNDs / ZnO represents the solution phosphor of the composite material of this patent, and the concentration of carbon nanodots in the two phosphors is the same. It can be seen from the figure that the phosphorescent biological imaging quality and imaging time of the composite material of this patent are significantly improved.

[0040] The composite material in this patent can be used to make phosphorescent ink, such as Fig.13 As shown, the printing comparison diagram of phosphorescent ink made of carbon nanodot single solution with the same concentration of carbon nanodots and phosphorescent ink made of composite material solution in this patent. Among them, InkA in the figure represents the ink containing carbon nanodot single solution, and InkB represents the ink containing composite material solution. It can be seen from the figure that the image displayed by the phosphorescent agent containing phosphorescent carbon nanodot composite material is clearer, brighter, and has better display effect.

Claims

1. A highly efficient phosphorescent water-soluble composite material, characterized in that: The composite material comprises zinc oxide nanocrystals and carbon nanodots. Calculated by mass, the mass of the zinc oxide nanocrystals: the mass of the carbon nanodots is 1-8:8; the zinc oxide nanocrystals are water-soluble zinc oxide nanocrystals, and the carbon nanodots are water-soluble carbon nanodots.

2. The high-efficiency phosphorescent water-soluble composite material according to claim 1, characterized in that: The composite material is liquid, and water-soluble zinc oxide nanocrystals and water-soluble carbon nanodots are dissolved in deionized water to form a mixed solution, wherein the mass concentration of the zinc oxide nanocrystals: the mass concentration of the carbon nanodots is 1-8:

8.

3. The high-efficiency phosphorescent water-soluble composite material according to claim 2, characterized in that: In the mixed solution, the mass concentration of the zinc oxide nanocrystal aqueous solution is 15-120 μg / mL; the mass concentration of the carbon nanodot aqueous solution is 120 μg / mL.

4. A method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics, comprising the following steps: a. Preparation of water-soluble zinc oxide nanocrystals; b. Preparation of water-soluble carbon nanodots; c. Mix According to the ratio of zinc oxide nanocrystal mass to carbon nanodot mass of 1-8:8, the materials obtained in step a and step b are mixed to obtain a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics.

5. The method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to claim 4, characterized in that: The step a further comprises the following steps: a1. The zinc oxide nanocrystals obtained in step a are dissolved in deionized water to prepare an aqueous solution of zinc oxide nanocrystals; The step b also includes the following steps: b1. The phosphorescent carbon nanodots obtained in step a are dissolved in deionized water to prepare a phosphorescent carbon nanodot aqueous solution; the step c is replaced by the following steps: c1. According to the mass concentration of zinc oxide nanocrystals: carbon nanodots, the mass concentration is 1 to 8:8, the solutions obtained in steps a1 and b1 are mixed, and the water-soluble carbon nanodots in the solution are sensitized by zinc oxide nanocrystals to obtain an efficient phosphorescent water-soluble composite material.

6. A method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to any one of claims 4 or 5, characterized in that: The water-soluble zinc oxide nanocrystal preparation process comprises the following steps: ① Solution preparation Disperse Zn(Ac)2 ∙2H2O in anhydrous ethanol and disperse KOH in anhydrous ethanol to prepare their respective alcohol solutions; ②Mixed reaction Add the KOH alcohol solution to the Zn(Ac)2 ∙2H2O alcohol solution and continue stirring for time T1 to form a mixed solution; ③ Water-soluble modification Add APTES to the mixed solution and continue stirring for T2. ④ Precipitation and centrifugation to obtain crude zinc oxide nanocrystals; ⑤ Wash the crude zinc oxide nanocrystals at least three times with anhydrous ethanol to remove impurities; ⑥ Drying to obtain water-soluble zinc oxide nanocrystalline powder.

7. The method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to claim 6, characterized in that: The preparation process of the Zn(Ac)2 ∙2H2O alcohol solution is as follows: 5.5 g Zn(Ac)2 ∙2H2O is dispersed in 150 mL anhydrous ethanol, and the preparation process of the KOH alcohol solution is as follows: 2.0 g KOH is dispersed in 20 mL anhydrous ethanol; the time T1 is 4 hours, the time T2 is 3 hours, and the drying temperature in step ⑥ is 70°C.

8. A method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to any one of claims 4 or 5, characterized in that: The water-soluble carbon nanodot preparation process comprises the following steps: A. Solution Preparation First dissolve ethylenediamine in deionized water. B. Carbonization to form carbon nanodots Then add phosphoric acid to the deionized water and stir for T3 to form a transparent solution A; put the transparent solution A into a microwave environment and heat it for T4 to carbonize the mixture in the solution; C. Dilution and centrifugation purification Take out in microwave environment, cool the solution to room temperature, add deionized water to dilute the solution, centrifuge for time T5 to take out the precipitate in the solution, and keep the liquid; D. After the liquid is filtered through a 0.22 μm ultrafiltration membrane, sodium carbonate is added to neutralize the acid in the liquid, and the supernatant is collected and dialyzed for time T6 E. Drying the dialyzed solution to obtain carbon nanodot powder; F. Silicon shell The aqueous solution of the carbon nanodot powder and tetraethoxysilane are dispersed in a deionized water supporting solution, and ammonia water is added to the solution, stirred at room temperature for time T7, and a transparent solution B is collected; G. The transparent solution B is filtered at least twice through a 0.22 μm ultrafiltration membrane to obtain a water-soluble carbon nanodot solution, and the solution is dried to obtain a water-soluble carbon nanodot powder.

9. The method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to claim 8, characterized in that: In the step A, 1 mL of ethylenediamine is dissolved in 15 mL of deionized water, 2 mL of phosphoric acid is added in the step B, and the stirring time T3 is 30 minutes; the heating time T4 in the microwave is 120 seconds; in the step C, 20 mL of deionized water is added for dilution, and the centrifugation time T5 is 10 minutes; the dialysis time in the step D is one week, and the dialysis is performed using a membrane with a MWCO of 500 Da.

10. The method for preparing a highly efficient phosphorescent water-soluble composite material having semiconductor nanocrystal sensitization characteristics according to claim 8, characterized in that: In the step, 0.1 mg / mL phosphorescent carbon nanodot aqueous solution and 0.5 mL tetraethoxysilane are dispersed in 15 mL deionized water to form a solution, 0.5 mL of ammonia water is added to the solution, and the stirring time T7 is 8 hours.